From Interactions to Conversations: The Development of Joint Engagement During Early Childhood. Issue 3 (22nd November 2013) - Adamson, Lauren B.; Bakeman, Roger; Deckner, Deborah F.; Nelson, P. Brooke
Abstract : This research traces the development of symbol‐infused joint engagement during mother–child interactions into the preschool years. Forty‐nine children, who had been previously observed as toddlers (L. B. Adamson, R. Bakeman, & D. F. Deckner, 2004 ), were systematically observed during interactions with their mothers at ages 3½, 4½, and 5½ during activities related to the past and future, internal states, and graphic systems. Although the amount of symbol‐infused joint engagement reached a ceiling by 3½, its focus continued to become more complex and its form more balanced. Individual differences in children's symbol‐infused joint engagement were stable across 4 years. These findings highlight both how joint engagement is transformed as conversational skills develop and how it remains rooted in earlier interactions and supported by caregiver's actions.